Aspectos da ecologia populacional do bivalve Anomalocardia brasiliana em região estuarina do semiárido do nordeste do Brasil - Maia, Allyssandra Maria Lima Rodrigues (Universidade Federal Rural do Semi-Árido, 2015)
The objective was to analyze aspects of population ecology (age structure, distribution, density, spatial and temporal evaluation) of bivalve Anomalocardia brasiliana in an estuary beaches of Rio Grande do Norte semiarid region. Samples were collected for 37 months (April / 09 to April / 12), which transects (placed in each collection) 300 m long in the region of intertidal established every 400 meters between them, were put in order extracting the shellfish and sediment for size analysis. Still were measured temperature and salinity of the water. We used the nonparametric Kruskal-Wallis and Wilcoxon rank sum subsequent test to check the differences in the density of A. brasiliana with respect to distance from the estuary (0, 400, 800, 1200 and 1600m). During the study (April / 09 to April / 12), the growth curves of A. brasiliana suggest the presence of nine well-defined cohorts, indicating a continuous play with recruitment peaks, growth parameters were estimated as L∞ = 30 45 mm and k = 1.00 y-1 and longevity of 4.88 years. The average values of density obtained ranged 26-322 plants / m2. The highest values were found in the average density of the shellfish from November / 2010 to July / 2011. In July / 11, the average density of individuals presented the highest value (322 ind / m2) that after a decrease in the months of August and September / 2011, these values tended to oscillate in October / November and December / 2011. It was verified at baseline, a lower density of A. brasiliana, especially in the months of April, May / 11, which was increasing during the study. Mean values were observed density in the months of June and July / 11, October and December / 11, which was probably related to the breeding period and recruitment of the species. It was also identified that, in the distance from 800 to 1600m estuary there was an increase in the density of individuals, during most months of collection. In the distance 0m estuary in almost every month, the occurrence of A. brasiliana was reduced or individuals were noted. The research showed that the prevalence of A. brasiliana, is probably related to the higher percentage of texture classes sand and very 25 fine, silt and clay sediment in which there is a preference for the species. The results showed that despite being which results in increased density of A. brasiliana, this still presents lower values than those found before the rains in 2008 and 2009, a period when the rain rate was very high, showing that the disorder affected the density of the species
Keywords: Densidade; Molusco; Estuário; Salinidade; Granulometria; Density; Shellfish; Estuary; Salinity; Grain size; CIENCIAS AGRARIAS::MEDICINA VETERINARIA